Analysis of the Influence of Leadership Style, Motivation and Supervision on the Performance of Anara Sky Kualanamu Hotel Employees - April Jaya Ndraha; Teguh Wahyono; Akhmad Taufik (International Journal of Society and Law, 2024)
Human resources are important assets in a company because they are responsible for running daily operations, ensuring company efficiency and productivity, and creating innovation and business growth. This study aims to determine whether leadership style, motivation and insight affect employee performance partially and simultaneously at Anara Sky Kualanamu Hotel. The approach used in this study is an associative approach. This research was conducted on employees of Anara Sky Kualanamu Hotel, with a total of 44 respondents with testing using SPSS ver 26. The results of this study show that the leadership style variable (X1) has a significant effect on employee performance, the motivation variable (X2) does not have a significant effect on employee performance, the supervisory variable (X3) does not have a significant effect on employee performance, the variables X1 (Leadership Style), X2 (Motivation), X3 (Supervision) simultaneously affect and significant employee performance.